Emotional labour strategies and employee performance: the role of emotional intelligence - Kamassi, Ahmed; Boulahlib, Loutfi; Abd. Manaf, Noor Hazilah; Omar, Azura (Emerald Group Publishing Ltd., 2019)
Purpose The purpose of this study is to examine the relationship between emotional labour (EL) strategies and employees’ performance by considering the role of emotional intelligence (EI) as a moderator.